Modeling and Performance Assessment of a Hypothetical Stand-Alone Parabolic Trough Solar Power Plant Supported by Climatic Measurements in Ipoh, Malaysia - Mohammad, S.T. (American Society of Mechanical Engineers (ASME), 2023)
This study presents a conceptual design for a concentrated solar power plant by using direct steam generation and a stand-alone power system based on a concentration of solar parabolic troughs. The system is located at the solar research site (SRS) of Universiti Teknologi PETRONAS in Ipoh, Malaysia. The model system uses an integrated turbine with 1.2 kW generators, and steam is generated by a flow loop powered by solar parabolic trough concentrators. An in-situ calculation of normal direct irradiance was conducted in SRS and used as an input for the mathematical model. The model was developed to assess the transient behavior of the system and the behavior of the projected power generation under seasonal variations and daily solar radiation. The parabolic trough power plant achieved the highest average output of 8.85 during the low rainfall season in March. Copyright Â© 2023 by ASME.